Effectiveness of Papaya (Carica papaya L.) Seed Extract and Alum on Aedes aegypti Larvae Death - Rini Ambarwati; Sara Nurmala; Nuning Anggraini (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2024)
People generally use larvicide to kill mosquito larvae. Synthetic chemical larvicides leave residues that have a negative impact on the environment. Therefore, research on natural larvicides has been developed to suppress the negative effects of chemical larvicides. Microparticle preparations can speed up the compound delivery system so that it will be effective in its use as a larvicide. The important composition in making microparticle preparations is polymer. The polymer used in this research is chitosan. The formulation of papaya seed extract and alum microparticles using chitosan polymer with the spray drying method was made into three formulas with different concentrations of extract and alum, namely formula 1 (0.1% : 0.05%), formula 2 (0.15% : 0.075%). %), and formula 3 (0.2% : 0.1%). The results obtained show that formula 3 with a concentration of 0.2% papaya seed extract and 0.1% alum has the best quality characteristics based on the polydispersity index parameters, namely 0.181, particle size 1233.67 nm, zeta potential value 72.6 mV. The number of samples was 500 test larvae consisting of 5 treatment groups. Each group contained 25 larvae and 4 replicates. The test larvae were observed after 24 hours and then analyzed. The test analysis carried out was the Probit test. The LC50 value obtained in this study was 95.5 ppm. These results indicate that the microparticle powder preparation has larvicidal efficacy against third/IV instar Aedes aegypti larvae.